PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS ARTIFICIAL INTELLIGENCE UNTUK PREDIKSI CASH FLOW PERUSAHAAN - Maulana Akmal Malik; Ratih Kusumastuti; Achmad Hizazi (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2026)
The rapid development of Artificial Intelligence (AI) technology has significantly transformed accounting information systems, particularly in financial data processing and analysis. One of the most affected areas is cash flow prediction, which plays a crucial role in corporate financial planning and decision-making. This study aims to examine the effect of implementing an Artificial Intelligence–based Accounting Information System (AIS) on the accuracy of cash flow prediction in service and trading companies located in Bandung City, Indonesia. This research employs a quantitative associative approach. Data were collected through questionnaires distributed to 60 respondents, consisting of accounting staff, financial supervisors, and financial managers. The data were analyzed using simple linear regression analysis to examine the relationship between the implementation of AI-based AIS and cash flow prediction accuracy. The results indicate that the implementation of AI-based AIS has a positive and significant effect on cash flow prediction accuracy, with a significance value of 0.000 and a coefficient of determination of 46.2%. These findings demonstrate that integrating Artificial Intelligence into accounting information systems enhances the accuracy, timeliness, and reliability of cash flow forecasts. This study contributes to the accounting information systems literature by providing empirical evidence on the strategic role of AI in improving financial planning and decision-making processes. Perkembangan teknologi Artificial Intelligence (AI) telah membawa perubahan signifikan dalam sistem informasi akuntansi, khususnya dalam pengolahan dan analisis data keuangan. Salah satu area yang paling terdampak adalah prediksi arus kas (cash flow), yang berperan penting dalam perencanaan dan pengambilan keputusan keuangan perusahaan. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan Sistem Informasi Akuntansi (SIA) berbasis AI terhadap akurasi prediksi arus kas pada perusahaan jasa dan dagang di Kota Bandung. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan asosiatif. Data diperoleh melalui penyebaran kuesioner kepada 60 responden yang terdiri dari staf akuntansi, supervisor, dan manajer keuangan. Teknik analisis data menggunakan regresi linier sederhana dengan bantuan analisis statistik. Hasil penelitian menunjukkan bahwa penerapan SIA berbasis AI berpengaruh positif dan signifikan terhadap akurasi prediksi cash flow dengan nilai signifikansi 0,000 dan koefisien determinasi sebesar 46,2%. Temuan ini membuktikan bahwa integrasi AI dalam sistem akuntansi mampu meningkatkan ketepatan, kecepatan, dan reliabilitas prediksi arus kas. Penelitian ini memberikan implikasi teoretis dan praktis terkait pentingnya adopsi teknologi AI dalam sistem akuntansi modern.